Прокляты и убиты: роман / Виктор Астафьев - Астафьев Виктор Петрович (Русская классика, 2022)
Экземпляры: (20220913) / Инвентарный номер: 42171 / Цена: 392.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: А 91 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6-44